2023
DOI: 10.1038/s41598-023-27789-9
|View full text |Cite
|
Sign up to set email alerts
|

Powdered and beaded sawdust materials modified iron (III) oxide-hydroxide for adsorption of lead (II) ion and reactive blue 4 dye

Abstract: The problems of lead and reactive blue 4 (RB4) dye contamination in wastewater are concerns because of their toxicities to aquatic life and water quality, so lead and RB4 dye removals are recommended to remove from wastewater before discharging. Sawdust powder (SP), sawdust powder doped iron (III) oxide-hydroxide (SPF), sawdust beads (SPB), and sawdust powder doped iron (III) oxide-hydroxide beads (SPFB) were synthesized and characterized with various techniques, and their lead or RB4 dye removal efficiencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
9
7
0
Order By: Relevance
“…This result agreed with the pH pzc results of this study which the pH pzc values of all materials were found at pH > 4. Moreover, it also corresponded to other previous studies that reported the highest lead removal efficiency at pH > 4 relating to pH pzc of lead adsorptions in an aqueous solution 33,37,45,46 . Therefore, pH 5 was the optimum pH of all sugarcane bagasse adsorbent materials which were used for studying the concentration effect.…”
Section: Batch Adsorption Experimentssupporting
confidence: 90%
See 3 more Smart Citations
“…This result agreed with the pH pzc results of this study which the pH pzc values of all materials were found at pH > 4. Moreover, it also corresponded to other previous studies that reported the highest lead removal efficiency at pH > 4 relating to pH pzc of lead adsorptions in an aqueous solution 33,37,45,46 . Therefore, pH 5 was the optimum pH of all sugarcane bagasse adsorbent materials which were used for studying the concentration effect.…”
Section: Batch Adsorption Experimentssupporting
confidence: 90%
“…In Fig. 6d, lead removal efficiencies of all materials were decreased with www.nature.com/scientificreports/ the increase of concentration because lead ions were more than the available active sites of bagasse adsorbent materials similar to the report by other studies 9,33,37,38,45 . Lead removal efficiencies from 5 to 30 mg/L of SB, SBF, SBB, and SBFB were 40.63-100%, 92.78-100%, 78.07-100%, and 96.19-100%, respectively.…”
Section: Batch Adsorption Experimentssupporting
confidence: 82%
See 2 more Smart Citations
“…The peels of potato, banana, and lemon are used as food waste adsorbents for lead removal [11][12][13] . For industrial wastes, sawdust, coal fly ash, and sugarcane bagasse fly ash have been used for removing lead and arsenic in an aqueous solution [14][15][16][17] . Therefore, adsorbents from waste are an interesting choice because not only they help to improve water quality for environmental remediation purposes but also using them is another benefit to waste treatment and management in terms of recycling natural resources.…”
mentioning
confidence: 99%